PENGARUH LINGKUNGAN KAMPUS DAN LITERASI DIGITAL TERHADAP KESIAPAN KERJA MAHASISWA OTOMOTIF - Yazid Zabian; Wahid Munawar (VOCATIONAL: Jurnal Inovasi Pendidikan Kejuruan, 2026)
ABSTRACT The transformation of the automotive industry toward digitally based working systems in the era of Industry 4.0 and Society 5.0 requires vocational education graduates to possess work readiness that is more adaptive to technological developments. However, the persistent gap between graduate competencies and industrial demands indicates that students’ work readiness is influenced not only by technical abilities but also by the quality of the learning environment and digital literacy skills. This study aims to analyze the influence of the campus environment and digital literacy on the work readiness of students in the Automotive Engineering Education Program at Universitas Pendidikan Indonesia, both partially and simultaneously. The study employed a quantitative approach using an explanatory survey design with an ex-post facto approach. The respondents consisted of 35 fourth- and sixth-semester students selected through a saturated sampling technique. Data were collected using a Likert-scale questionnaire distributed via Google Forms and analyzed through multiple linear regression using IBM SPSS 25. The findings revealed that both the campus environment and digital literacy had a positive and significant effect on students’ work readiness. Digital literacy emerged as the most dominant variable, particularly in supporting technological adaptation, digital information management, and readiness to face technology-based modern working systems. In addition, both variables simultaneously contributed strongly to the development of students’ work readiness in the automotive field. These findings emphasize that the development of vocational automotive education should be directed toward strengthening industry-oriented learning environments and integrating digital literacy into the learning process to produce graduates who are more competitive, adaptive, and relevant to the needs of the modern automotive industry. ABSTRAK Perubahan industri otomotif menuju sistem kerja berbasis digital pada era industri 4.0 dan Society 5.0 menuntut lulusan pendidikan vokasi memiliki kesiapan kerja yang lebih adaptif terhadap perkembangan teknologi. Namun, masih adanya kesenjangan antara kompetensi lulusan dan kebutuhan industri menunjukkan bahwa kesiapan kerja mahasiswa tidak hanya dipengaruhi kemampuan teknis, tetapi juga faktor lingkungan belajar dan penguasaan teknologi digital. Penelitian ini bertujuan menganalisis pengaruh lingkungan kampus dan literasi digital terhadap kesiapan kerja mahasiswa Pendidikan Teknik Otomotif Universitas Pendidikan Indonesia, baik secara parsial maupun simultan. Penelitian menggunakan pendekatan kuantitatif dengan desain survei eksplanatori dan pendekatan ex-post facto. Responden penelitian berjumlah 35 mahasiswa semester 4 dan 6 yang ditentukan menggunakan teknik sampling jenuh. Data dikumpulkan melalui kuesioner skala Likert berbasis Google Form dan dianalisis menggunakan regresi linear berganda dengan bantuan IBM SPSS 25. Hasil penelitian menunjukkan bahwa lingkungan kampus dan literasi digital sama-sama berpengaruh positif dan signifikan terhadap kesiapan kerja mahasiswa. Literasi digital menjadi variabel yang memiliki pengaruh paling dominan, terutama dalam mendukung kemampuan adaptasi teknologi, pengelolaan informasi digital, dan kesiapan menghadapi sistem kerja modern berbasis teknologi. Selain itu, kedua variabel secara simultan memberikan kontribusi kuat terhadap pembentukan kesiapan kerja mahasiswa otomotif. Temuan penelitian menegaskan bahwa pengembangan pendidikan vokasi otomotif perlu diarahkan pada penguatan lingkungan belajar berbasis industri dan integrasi literasi digital agar lulusan lebih kompetitif, adaptif, dan relevan dengan kebutuhan industri modern.